Efficacy of Yijinjing-inspired exercises on sleep disorders in Parkinson’s disease: a controlled fNIRS study - Hu, Zekai; Shi, Jing; Wang, Jinyan; Liu, Ting; Li, Yujia; Xue, Han; Jin, Xueming; Xue, Yiting; Wang, Jie; Liu, Xinhao; Hu, Jun (Frontiers in Psychiatry, 2025)
BackgroundSleep disorders are prevalent in Parkinson's disease (PD) patients, significantly impacting their quality of life and rehabilitation outcomes. This controlled trial aimed to investigate the impact of Yijinjing-inspired exercises on sleep disorders in PD patients, utilizing functional near-infrared spectroscopy (fNIRS) to assess neurophysiological changes.MethodsNinety-six PD patients were allocated to control, exercise, or music therapy groups for eight weeks. The Pittsburgh Sleep Quality Index (PSQI), along with the Montreal Cognitive Assessment (MoCA), Mini-Mental State Examination (MMSE), Unified Parkinson's Disease Rating Scale (UPDRS), and Parkinson's Disease Questionnaire (PDQ-39) were used to assess outcomes. fNIRS measured neurophysiological changes post-intervention.ResultsThe exercise group demonstrated substantial improvement in sleep quality after Bonferroni correction (PSQI: mean Δ = -1.78 ± 0.99, P < 0.001; Cohen's d = 1.45). Moderate effect sizes were observed in cognition (MoCA: d = 0.43) and motor function (UPDRS: d = 0.40), though these did not retain statistical significance after correction. Between-group analysis revealed greater PSQI reduction in exercise versus control (Δ = -1.19 ± 0.85 vs. -0.19 ± 1.53; P = 0.001 after Bonferroni adjustment, Cohen's d = 0.87), but not versus music therapy (P = 0.018 > 0.0167). fNIRS confirmed cortical reorganization in dorsolateral prefrontal cortex (Brodmann Area 9; Channel 3) and primary motor cortex (Brodmann Area 4; Channel 9) at FDR-corrected P < 0.05. The control group showed no statistically significant changes post-correction (all P > 0.01).DiscussionYijinjing training may improve sleep quality in Parkinson's disease patients, with preliminary evidence of neuroplastic adaptation. Consideration could be given to exploring its integration into comprehensive rehabilitation approaches.